Assessment engine oil using UKM acoustic emission energy viscosity model(ηEAEUKM). - Inayatullah, Othman; Jamaludin, Nordin; Mohd Nor, Mohd Jailani; Mat, Fauziah; Baharuddin, Aziz (2012)
Estimation the diesel engine oil viscosity in an engine operation is very important since it affects the engine performance. One of the most promising engine oil viscosity monitoring methods is based on the analysis of acoustic emission(AE) signals, which is an extremely powerful technique that canbe deployed in a wide range of application of non-destructive testing. This technique is already used for monitoring the behavior of the sliding activities almost in all bearing operations especially wear. But in this study, the AE signals were applied for monitoring and estimate diesel engine oil viscosity by using new equation which is known as UKM acoustic emission energy viscosity model (ηEAEUKM). The AE signals generated in the piston sliding zone on engine oil surface and it’s very sensitive for correlation with engine oil viscosity. Using MATLAB, the AE signals could be translated into AE energy. By using UKM acoustic emission energy viscosity model (ηEAEUKM) newly introduced, viscosity value will be accessible of AE energy. This study was carried out with a single cylinder 4 strokes diesel engine. That engine oil also undergoes oil analysis to seek the real viscosity value as study comparison. Analysis showed that the UKM acoustic emission energy viscosity model (ηEAEUKM) is applicable for estimation diesel engine oil viscosity.